Preparation of polylactide-co-glycolide nanoparticles incorporating celecoxib and their antitumor activity against brain tumor cells - Jung S. (Dove Medical Press, 2011)
Tae-Ho Kim1*, Young-Il Jeong2*, Shu-Guang Jin2, Jian Pei2, Tae-Young Jung1, Kyung-Sub Moon1, In-Young Kim1, Sam-Suk Kang1, Shin Jung1,21Department of Neurosurgery, 2Brain Tumor Research Laboratory, Chonnam National University Research Institute of Medical Science, Chonnam National University Hwasun Hospital and Medical School, Gwangju, Republic of Korea *These authors contributed equally to this work. Background: Celecoxib, a cyclo-oxygenase (COX)-2 inhibitor, has been reported to mediate growth inhibitory effects and to induce apoptosis in various cancer cell lines. In this study, we examined the potential effects of celecoxib on glioma cell proliferation, migration, and inhibition of COX-2 expression in vitro. Methods: Celecoxib was incorporated into poly DL-lactide-co-glycolide (PLGA) nanoparticles for antitumor drug delivery. Results: PLGA nanoparticles incorporating celecoxib had spherical shapes and their particle sizes were in the range of 50–200 nm. Drug-loading efficiency was not significantly changed according to the solvent used, except for acetone. Celecoxib was released from the PLGA nanoparticles for more than 2 days, and the higher the drug content, the longer the duration of drug release. PLGA nanoparticles incorporating celecoxib showed cytotoxicity against U87MG tumor cells similar to that of celecoxib administered alone. Furthermore, celecoxib did not affect the degree of migration of U87MG cells. PLGA nanoparticles incorporating celecoxib showed dose-dependent cytotoxicity similar to that of celecoxib alone in C6 rat glioma cells. Western blot assay of the C6 cells showed that neither celecoxib alone nor PLGA nanoparticles incorporating celecoxib affected COX-2 expression. Conclusion: PLGA nanoparticles incorporating celecoxib had antitumor activity similar to that of celecoxib alone, even though these particles did not affect the degree of migration or COX-2 expression in the tumor cells. Keywords: celecoxib, cyclo-oxygenase-2, PLGA nanoparticles, glioma, antitumor activity